Potensi Pare (Momordica charantia L) Sebagai Penurun Kadar Kolesterol Darah - Raynaldo Lisius Marbun (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Nowadays, daily food consumption is shifting towards food patterns that contain high cholesterol levels such as fast food, sea food, and others. Foods that contain saturated fatty acids play the most role in raising blood cholesterol levels. Excess cholesterol causes the deposition of cholesterol in the walls of blood vessels which causes narrowing and hardening of the arteries known as atherosclerosis which is the presence of plaque in blood vessels. The continued narrowing process causes the death of heart muscle tissue called myocardial infarction and if it expands it will cause heart failure. In men aged mid 40 years and over with high serum cholesterol levels (cholesterol> 240 mg / dL and LDL cholesterol> 160 mg / dL) the risk of coronary heart disease (CHD) will be greatly increased. In Indonesia, one of the cardiovascular diseases that continues to rank first is coronary heart disease. According to world statistics, there are 9.4 million deaths each year caused by cardiovascular disease and 45% of these deaths are caused by coronary heart disease. It is estimated that the number will increase to 23.3 million by 2030.. Efforts to prevent and treat cardiovascular disease can be done by consuming fruits such as Momordica charantia (bitter melon) antioxidant content contained in saponins, flavonoids, polyphenols, vitamins A, B, and C in bitter melon to prevent atherosclerosis by inhibiting LDL oxidation.